Optimalisasi Pengelolaan Inventaris Melalui Aplikasi Berbasis Website pada SMK Negeri 1 Bintan Timur - Saputra, Aggry; Saidah, Muthiah As; Setiawan, Hendi (LPPM Universitas Putera Batam, 2024)
SMK Negeri 1 Bintan Timur is a vocational high school under the auspices of the Bintan District Education Office. The process of recording inventory items for facilities, infrastructure, and books at SMK Negeri 1 Bintan Timur is done manually by recording them in books. This manual recording process has resulted in several problems, such as lengthy inventory data retrieval processes and the risk of lost records. The system proposed in this study can record the borrowing and returning of inventory items for facilities, infrastructure, and books in the library. This system can assist in the inventory data recording process to minimize the risk of recording errors and data loss